Murder and moonshine : a mystery - Miller, Carol, 1972- (Minotaur Books,a Thomas Dunne book, 2013)
"All small towns have secrets--and plenty of them--as every small town waitress knows. Daisy is no different. A young, recently-separated waitress at H&P's Diner in sleepy southwestern Virginia, she hears more than her fair share of neighborhood gossip while serving plates of hash and peach cobbler. But when a reclusive old man, Dickerson, shows up at the diner one day, only to drop dead a few minutes later, Daisy quickly learns that some secrets are more dangerous to keep than others--especially when there's money and moonshine involved." --